Coumarin hybrid derivatives as promising leads to treat tuberculosis: Recent developments and critical aspects of structural design to exhibit anti-tubercular activity. (March 2021) - Reddy, Dinesh S.; Kongot, Manasa; Kumar, Amit
Abstract: Tuberculosis (TB) is a highly contagious airborne disease with nearly 25% of the world's population infected with it. Challenges such as multi drug resistant TB (MDR-TB), extensive drug resistant TB (XDR-TB) and in rare cases totally drug resistant TB (TDR-TB) emphasizes the critical and urgent need in developing novel TB drugs. Moreover, the prolonged and multi drug treatment regime suffers a major drawback due to high toxicity and vulnerability in TB patients. This calls for intensified research efforts in identifying novel molecular scaffolds which can combat these issues with minimal side effects. In this pursuit, researchers have screened many bio-active molecules among which coumarin have been identified as promising candidates for TB drug discovery and development. Coumarins are naturally occurring compounds known for their low toxicity and varied biological activity. The biological spectrum of coumarin has intrigued medicinal researchers to investigate coumarin scaffolds for their relevance as anti-TB drugs. In this review we focus on the recent developments of coumarin and its critical aspects of structural design required to exhibit anti-tubercular (anti-TB) activity. The information provided will help medicinal chemists to design and identify newer molecular analogs for TB treatment and also broadens the scope of exploring future generation potent yet safer coumarin based anti-TB agents. Graphical abstract: Image 1 Highlights: TB-bacteria are becoming resistance to almost all drugs. Coumarin derivatives a promising lead to treat TB. Recent developments of coumarin analogs as potent anti-TB agents. SAR studies of coumarin derivatives to exhibit anti-TB activity. This review will help to identify and design new molecular analogs for TB treatment.